BCl(3)‐Induced Annulative Oxo‐ and Thioboration for the Formation of C3‐Borylated Benzofurans and Benzothiophenes - Warner, Andrew J. (Angew Chem Int Ed Engl, 2016)
BCl(3)‐induced borylative cyclization of aryl‐alkynes possessing ortho‐EMe (E=S, O) groups represents a simple, metal‐free method for the formation of C3‐borylated benzothiophenes and benzofurans. The dichloro(heteroaryl)borane primary products can be protected to form synthetically ubiquitous pinacol boronate esters or used in situ in Suzuki–Miyaura cross couplings to generate 2,3‐disubstituted heteroarenes from simple alkyne precursors in one pot. In a number of cases alkyne trans‐haloboration occurs alongside, or instead of, borylative cyclization and the factors controlling the reaction outcome are determined.